Online public attention toward allergic rhinitis in Wuhan, China: Infodemiology study using Baidu index and meteorological data - Wang, Yunfei; Gao, Ziang; Lv, Hao; Xu, Yu (Frontiers in Public Health, 2022)
Background: With the popularization of the Internet and medical knowledge, more and more people are learning allergic rhinitis (AR) through the Internet. Objective: This study aims to analyze the epidemiological characteristics and online public attention to AR in Wuhan, China, utilizing the most popular search engine in mainland China and meteorological data of Wuhan. Methods: To study the Internet attention and epidemiological characteristics of AR in Wuhan, the search volume (SV) of "Allergic Rhinitis" in Mandarin and AR-related search terms from January 1, 2014 through December 31, 2021 were recorded. For user interest, the search and demand data were collected and analyzed. Results: The yearly average Baidu SV of AR in both Wuhan and China increased year by year but began to decline gradually after the COVID-19 pandemic. Baidu SV of AR in Wuhan exhibited significant seasonal variation, with the first peak was from March to May and the second peak occurring between September and October. Correlation analysis revealed a moderate positive correlation between the monthly average SV of “Allergic Rhinitis” and “Mites” and “Mites + Pollen Allergy” in Wuhan, a low positive correlation between the monthly average SV of “Allergic Rhinitis” and “Pollen Allergy”, and a significant positive correlation between monthly SV of “Allergic Rhinitis” and the meteorological index of pollen allergy (MIPA). Conclusions: The attention given to the topic on the internet, as measured by the number of search volume, was reflective of the situation in Wuhan, China. It has the potential to predict the epidemiological characteristics of AR and help medical professionals more effectively make seasonal AR health education.